Immunoproteasomes control activation of innate immune signaling and microglial function - Çetin, Gonca; Studencka-Turski, Maja; Venz, Simone; Schormann, Eileen; Junker, Heike; Hammer, Elke; Völker, Uwe; Ebstein, Frédéric; Krüger, Elke (Frontiers in Immunology, 2022)
Microglia are the resident immune cells of the central nervous system (CNS) and play a major role in the regulation of brain homeostasis. To maintain their cellular protein homeostasis, microglia express standard proteasomes and immunoproteasomes (IP), a proteasome isoform that preserves protein homeostasis also in non-immune cells under challenging conditions. The impact of IP on microglia function in innate immunity of the CNS is however not well described. Here, we establish that IP impairment leads to proteotoxic stress and triggers the unfolded and integrated stress responses in mouse and human microglia models. Using proteomic analysis, we demonstrate that IP deficiency in microglia results in profound alterations of the ubiquitin-modified proteome among which proteins involved in the regulation of stress and immune responses. In line with this, molecular analysis revealed chronic activation of NF-κB signaling in IP-deficient microglia without further stimulus. In addition, we show that IP impairment alters microglial function based on markers for phagocytosis and motility. At the molecular level IP impairment activates interferon signaling promoted by the activation of the cytosolic stress response protein kinase R. The presented data highlight the importance of IP function for the proteostatic potential as well as for precision proteolysis to control stress and immune signaling in microglia function.